An Asynchronous Peer Support Intervention for Men experiencing Unipolar Depression; Development of a Complex intervention. - Brydges, Sarah (2023)
This study set out to develop a complex intervention, delivered in a community pharmacy setting that can support men prescribed antidepressants for depression.